2019
DOI: 10.1002/jbt.22328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of allyl isothiocyanate on insulin resistance, oxidative stress status, and transcription factors in high‐fat diet/streptozotocin‐induced type 2 diabetes mellitus in rats

Abstract: Allyl isothiocyanate (AITC), a dietary phytochemical found in some cruciferous vegetables, is commonly used as an antimicrobial, anticancer, and antioxidant agent.In the present study, we investigated the effects of AITC on insulin resistance and transcription factors in a diabetic rat model. A total of 42 Wistar rats were divided into six groups and orally treated for 12 weeks as follows: (i) control; (ii) AITC (100 mg/kg body weight [BW]); (iii) high fat diet (HFD); (iv) HFD + AITC (100 mg/kg BW); (v) HFD + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
3
32
1
Order By: Relevance
“…Other corroborating evidences are the increased inflammatory markers (NF-κB, TNFα, IL-6, and IL-10) reported in cortical tissues of murine diabetes models [201][202][203], HK2 cell cultures under high glucose environment (NF-κB) [204], and cortical portions of T2D patients (NF-κB) [202]. These elevated markers were associated with disrupted insulin signalling characterized by high FOXO1 and reduced AKT [202], PPARγ, and ISRS1 [201,203] but maintained ISR2 levels [201]. Increased renal gluconeogenesis [202], as expected, and reduced GLUT2 [203] were also associated with enhanced inflammatory markers.…”
Section: Glucose Effects On Renal Glucosesupporting
confidence: 54%
See 2 more Smart Citations
“…Other corroborating evidences are the increased inflammatory markers (NF-κB, TNFα, IL-6, and IL-10) reported in cortical tissues of murine diabetes models [201][202][203], HK2 cell cultures under high glucose environment (NF-κB) [204], and cortical portions of T2D patients (NF-κB) [202]. These elevated markers were associated with disrupted insulin signalling characterized by high FOXO1 and reduced AKT [202], PPARγ, and ISRS1 [201,203] but maintained ISR2 levels [201]. Increased renal gluconeogenesis [202], as expected, and reduced GLUT2 [203] were also associated with enhanced inflammatory markers.…”
Section: Glucose Effects On Renal Glucosesupporting
confidence: 54%
“…These elevated markers were associated with disrupted insulin signalling characterized by high FOXO1 and reduced AKT [202], PPARγ, and ISRS1 [201,203] but maintained ISR2 levels [201]. Increased renal gluconeogenesis [202], as expected, and reduced GLUT2 [203] were also associated with enhanced inflammatory markers.…”
Section: Glucose Effects On Renal Glucosesupporting
confidence: 52%
See 1 more Smart Citation
“…Additionally, Abdulmalek and Balbaa in 2019 examined the potential of selenium and found that it promoted insulin sensitivity by ameliorating inflammation and oxidative stress in diabetic rats [140]. These data complement the results of basic studies suggesting oxidative stress induces insulin resistance and DM [97,123,132,137,139,140]. Whilst relatively few, there is clinical evidence supporting the animal studies [141].…”
Section: Animal Studies and The Effect Of Reducing Oxidative Stressmentioning
confidence: 87%
“…One study with a randomized double-blind placebo-controlled design. 6 Oxidative Medicine and Cellular Longevity and inflammatory responses in diabetic rats [139]. Additionally, Abdulmalek and Balbaa in 2019 examined the potential of selenium and found that it promoted insulin sensitivity by ameliorating inflammation and oxidative stress in diabetic rats [140].…”
Section: Animal Studies and The Effect Of Reducing Oxidative Stressmentioning
confidence: 99%